Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

MDSN-Net: A multi-domain spectral nexus network for underwater accurate fish counting - Jiaming Xin; Tongtong Gu; Zhengmeng Wu; Yiying Wang; Dashe Li; Huanhai Yang (Computers and Electronics in Agriculture, 2026)

How built environments shape leisure jogging styles: Nonlinear and interactive effects across objective and subjective dimensions - Wei Yang; Mengjia Yin; Longyang Huang; Jiaming Sun; Caixuan Guo; Xin Fan; Jingjing Li (Journal of Transport Geography, 2026)

Structured wave-transparent metamaterials for simultaneous broadband electromagnetic and acoustic absorption - Tongtong Zhang; Qingxuan Liang; Yubing Duan; Xin Yan; Aoqi Ren; Jiaming Feng; Dichen Li (Chemical Engineering Journal, 2026)

Morphology–aware spatiotemporal prediction of cumulonimbus–related radar echoes using CSDP–Net - Deyi Wang; Xu Wang; Zhenhong Cheng; Xin Chang; Hongping Yuan; Jixiang Yang; Yi Liang; Jiaming Hu; Ting Zhang (Theoretical and Applied Climatology, 2026)

Br radicals generated via bromate-free photoactivation may promote degradation of emerging contaminants in highly saline waters - Min Zhao; Jiaming Gan; Yingdong Li; Mingbao Feng; Hamid Mohammed Al-Gabr; Xin Yu; Lei Wang (Water Research, 2026)

Unlocking ultrahigh anion adsorption in sunlight-responsive metal-organic frameworks for water purification - Xu Wu; Qian Guan; Mengyu Tang; Yilei Fang; Jiaming Gan; Xinyu Zhang; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

An efficient fish counting method with adaptive global perception and multi-scale feature perception - Yiying Wang; Dashe Li; Jiaming Xin (Aquacultural Engineering, 2025)

Large-area crack-free photonic crystals coating on leather with brilliant and robust iridescent structural color - Jingyuan Hu; Yaqun Han; Xin Sun; Wenbo Wu; Jiaming Huyan; Suli Wu (Chemical Engineering Journal, 2025)

Spatial-temporal evolution of landslides spanning the impoundment of Baihetan mega hydropower project revealed by satellite radar interferometry - Jiaming Yao; Teng Wang; Xin Yao (Remote Sensing of Environment, 2025)

Design and interaction dynamics analysis of a novel hybrid bending-twisting-pulling end-effector for robotic tomato picking - Jiaming Fang; Nianzu Dai; Zhenbo Xin; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

Building block design of thermally regenerable metal–organic framework composites for highly selective lithium adsorption - Xinyu Zhang; Xu Wu; Jiaming Gan; Xin Yu; Huanting Wang; Ranwen Ou (Chemical Engineering Journal, 2024)

Assessing geological hazard susceptibility and impacts of climate factors in the eastern Himalayan syntaxis region - Jiaming Yao; Yanbing Wang; Teng Wang; Beibei Zhang; Yuming Wu; Xin Yao; Zheng Zhao; Shu Zhu (Landslides, 2024)

LSGNet: A lightweight convolutional neural network model for tomato disease identification - Shengxian Yang; Licai Zhang; Jianwu Lin; Tomislav Cernava; Jitong Cai; Renyong Pan; Jiaming Liu; Xingtian Wen; Xiaoyulong Chen; Xin Zhang (Crop Protection, 2024)

Effects of polymerization types on plastics ingestion and biodegradation by Zophobas atratus larvae, and successions of both gut bacterial and fungal microbiomes - Yue Weng; Xiaoyu Han; Huayang Sun; Jiaming Wang; Yumeng Wang; Xin Zhao (Environmental Research, 2024)

Alterations in Dynamic Functional Connectivity in Patients with Cerebral Small Vessel Disease - Futao Chen; Qian Chen; Yajing Zhu; Cong Long; Jiaming Lu; Yaoxian Jiang; Xin Zhang; Bing Zhang (Translational Stroke Research, 2024)
Cerebral small vessel disease (CSVD) is a common disease that seriously endangers people’s health, and is easily overlooked by both patients and clinicians due to its near-silent onset. Dynamic functional connectivity (DFC) is a new concept focusing on the dynamic features and patterns of brain networks that represents a powerful tool for gaining novel insight into neurological diseases. To assess alterations in DFC in CSVD patients, and the correlation of DFC with cognitive function. We enrolled 35 CSVD patients and 31 normal control subjects (NC). Resting-state functional MRI (rs-fMRI) with a sliding-window approach and k -means clustering based on independent component analysis (ICA) was used to evaluate DFC. The temporal properties of fractional windows and the mean dwell time in each state, as well as the number of transitions between each pair of DFC states, were calculated. Additionally, we assessed the functional connectivity (FC) strength of the dynamic states and the associations of altered neuroimaging measures with cognitive performance. A dynamic analysis of all included subjects suggested four distinct functional connectivity states. Compared with the NC group, the CSVD group had more fractional windows and longer mean dwell times in state 4 characterized by sparse FC both inter-network and intra-networks. Additionally, the CSVD group had a reduced number of windows and shorter mean dwell times compared to the NC group in state 3 characterized by highly positive FC between the somatomotor and visual networks, and negative FC in the basal ganglia and somatomotor and visual networks. The number of transitions between state 2 and state 3 and between state 3 and state 4 was significantly reduced in the CSVD group compared to the NC group. Moreover, there was a significant difference in the FC strength between the two groups, and the altered temporal properties of DFC were significantly related to cognitive performance. Our study indicated that CSVD is characterized by altered temporal properties in DFC that may be sensitive neuroimaging biomarkers for early disease identification. Further study of DFC alterations could help us to better understand the progressive dysfunction of networks in CSVD patients.

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Hyporheic exchange in a compound channel under unsteady flow: Numerical simulations - Jiaming Liu; Yang Xiao; Pei Xin; Nairu Wang; Saiyu Yuan; Taotao Zhang; Chentao Li; Carlo Gualtieri (Journal of Hydrology, 2024)

Weather data-centric prediction of maize non-stressed canopy temperature in semi-arid climates for irrigation management - Hope Njuki Nakabuye; Daran R. Rudnick; Kendall C. DeJonge; Katherine Ascough; Wei-zhen Liang; Tsz Him Lo; Trenton E. Franz; Xin Qiao; Abia Katimbo; Jiaming Duan (Irrigation Science, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

High-efficient photocatalytic degradation of multiple pollutants by CdPS3 nanosheets - Bingda Li; Jiaming Song; Yuting Li; Chaoying Meng; Shuxian Wang; Linghao Zong; Honggang Ye; Yishuai Jing; Feng Teng; Peng Hu; Haibo Fan; Guangde Chen; et al. (Process Safety and Environmental Protection, 2024)

Kinetic modeling and mechanisms of parahalogenated phenols degradation by UV222/H2O2 - Min Zhao; Ting Li; Yizhan Zhang; Jiaming Gan; Yiting Zhao; Xin Yu; Lei Wang (Journal of Cleaner Production, 2024)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Effects of dietary vitamin E supplementation on growth performance, slaughter performance, antioxidant capacity and meat quality characteristics of finishing bulls - Jiaming Luan; Yinghai Jin; Tai Zhang; Xin Feng; Kai Geng; Min Zhang; Chunyin Geng (Meat Science, 2023)

A novel fish CRADD inhibits Singapore grouper iridovirus (SGIV) infection by mediating apoptosis and modulating SGIV CARD (VP48)-caspase-2 interaction - Xin Zhang; Siting Wu; Zetian Liu; Jiaming Liao; Jingguang Wei; Qiwei Qin (Aquaculture, 2023)

Ingestion preference and efficiencies of different polymerization types foam plastics by Tenebrio molitor larvae, associated with changes of both core gut bacterial and fungal microbiomes - Yijing Wang; Xin Zhao; Jiaming Wang; Yue Weng; Yumeng Wang; Xin Li; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2023)

Comparing extraction methods for analyzing n-alkyl lipids in shelf sediments from the China Sea - Jiaming Zhou; Xiaoxiao Zhao; Xin Chen; Liang Dong (Organic Geochemistry, 2023)

Establishment and characterization of a brain tissue cell line from spotted knifejaw ( Oplegnathus punctatus ) and its susceptibility to several fish viruses - Jiaming Liao; Xin Zhang; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Journal of Fish Diseases, 2023)
Cells are important in the study of virus isolation and identification, viral pathogenic mechanisms and antiviral immunity. The spotted knifejaw ( Oplegnathus punctatus ) is a significant farmed fish in China that has been greatly affected by diseases in recent years. In this study, a new cell line derived from the spotted knifejaw brain (SKB) was established and characterized. SKB cells multiplied well in Leibovitz's L‐15 medium supplemented with 10% fetal bovine serum at 28°C. Chromosome analysis revealed that modal chromosome number was 48 for SKB. SKB cells exhibit susceptibility to several fish viruses, such as a largemouth bass virus, red grouper nervous necrosis virus (RGNNV), infectious spleen and kidney necrosis virus (ISKNV), Singapore grouper iridovirus (SGIV) and spotted knifejaw iridovirus isolate (SKIV‐TJ), as shown by cytopathic effect and increased viral titers. Electron microscopy results showed that the cytoplasm contained a large number of vacuoles, and many virus particles existed at the edge of the vacuoles in RGNNV‐infected cells and numerous viral particles were scattered throughout the cytoplasm in both ISKNV‐ and SKIV‐TJ‐infected cells. These results suggest that SKB is an ideal tool for studying host–virus interactions and potential vaccine development.

Superiority of UV222 radiation by in situ aquatic electrode KrCl excimer in disinfecting waterborne pathogens: Mechanism and efficacy - Ting Li; Yizhan Zhang; Jiaming Gan; Xin Yu; Lei Wang (Journal of Hazardous Materials, 2023)

In-depth understanding of catalytic and adsorbing effects in polysulfides conversion and rationally designing coaxial nanofibers for Li-S batteries - Jiaming Tian; Zihan Shen; Huiting Cheng; Xin Jin; Zhonghua Li; Yang Wen; Junfeng Hui; Shaohua Guo; Huigang Zhang; Qingshan Zhu (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Surfactant-induced photocatalytic performance enhancement of europium oxide nanoparticles - Yishuai Jing; Tianxin Kang; Peng Hu; Haibo Fan; Feng Teng; Xin Zhao; Jiaming Song (Process Safety and Environmental Protection, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

Diverse transcriptional patterns of homoeologous recombinant transcripts in triploid fish (Cyprinidae) - Li Ren; Xueyin Zhang; Jiaming Li; Xiaojing Yan; Xin Gao; Jialin Cui; Chenchen Tang; Shaojun Liu (Science China Life Sciences, 2021)

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Analysis of deformation characteristics for a reservoir landslide before and after impoundment by multiple D-InSAR observations at Jinshajiang River, China - Lingjing Li; Xin Yao; Jiaming Yao; Zhenkai Zhou; Xin Feng; Xinghong Liu (Natural Hazards, 2019)

Bank gully extraction from DEMs utilizing the geomorphologic features of a loess hilly area in China - Xin Yang; Jiaming Na; Guoan Tang; Tingting Wang; Axing Zhu (Frontiers of Earth Science, 2019)